In Vitro Propagation Studies on the Initial and Establishment Stages of Rubber (Hevea Brasiliensis Muell. Arg.) - Rodriguez, Alejandro Flores (1997)
Development of in vitro methods to propagate rubber is highly desirable. Some procedures exist but they generally do not address well the initial and establishment stages. This leads to minimal arrest of two common deterrents in any micropropagation system, i.e., contamination and browning. This project attempted to study both contamination and browning phenomena with an aim of improving survival without altering regeneration of explants. Field materials of clone RRIM 600 were used. Experiments on the Initial and Establishment stages, their interactions and concluding experiments were conducted. In all experiments, explants were cultured in the standard tissue culture procedures on basic MS medium. In the Initial stage, the results showed no significant difference between chemical treatments of antibiotics and/or fungicide in the field and control. As for the physical characteristics, efficient initial measures were to use 6-week old middle portions or shoot tips. This could be improved by growing these explants in a glasshouse. In the Establishment stage, the most efficient procedure to decontaminate explants was Procedure E that included a succession of treatments with ethanol, Clorox, Rifampicin, Ampicillin, DMSO and Triton-X before culturing. Regarding debrowning treatments, the best overall responses were obtained by culturing explants in MS medium (half strength) modified by the addition of 4 mg/L silver nitrate. In the analysis of the interactions between treatments in the Initial and Establishment stages, results showed that the combination of treatments with better potential was the one that included the use of mature explants (6-week old) surface decontaminated by Procedure E.